The Potential and Effectiveness of Snail Seromucoid and Chitosan as Bioimmunostimulators - Harti, Agnes Sri; Sutanto, Yusup Subagio; Puspawati, Nony (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2022)
The host's cellular immune response plays an important role in the process of eliminating microorganisms that cause infection. Substances that can stimulate an increase in the immune response are called immunostimulators. Snail seromucoid contains bioactive compounds such as glycans, peptides, glycopeptides and chondroitin sulfate. Chitosan as an antimicrobial agent can be used in the biomedical field because chitosan has a number of hydroxyl groups (OH) and amine groups (NH2). The research objective was to determine the potency and effectiveness of snail seromucoid and chitosan as bioimmunostimulators. The research method is based on laboratory experimental results with the research stages, namely the analysis of the effectiveness of seromucoid and chitosan on lymphocyte proliferation. The results of the one way ANOVA analysis showed a p value of 0.000 so that there was a significant effect between the treatment groups, namely the effect of giving chitosan 65 ug/ml; snail mucus 65 ug/mL and a combination of chitosan (65 ug/mL) and snail mucus (65 ug/mL) ratio of 1:1, can increase lymphocyte proliferation optimally. This shows that snail mucus, chitosan and their combination in a 1:1 ratio are effective as BRM (Biological Response Modifier). It is hoped that the contribution of the results of this study can be further developed in the bioformulation of snail seromucoid preparations and chitosan as therapeutic agents for infectious diseases, including Acute Respiratory Distress Syndrome (ARDS), Tuberculosis and other diseases.